RAPPORTRYERS Inventory of documents - (:unkn) unknown (ARCA, 2018)
Emerged from the ranks of the Rapportryers that was involved in the inauguration of the Voortrekker Monument in 1949; Federation of Rapportryerskorpse was established in August 1960
COVERAGE 1961- ; 26.50 metre; unsorted accretion
Keywords: RAPPORTRYERS; Inventories